Work and Friendship Ties in Organizations: A Comparative Analysis of Relation Networks - Lincoln, James R.; Miller, Jon (Administrative Science Quarterly, 1979)
Perhaps the key alternative strategy we have in mind is that implied in the methodologies of White, Boorman, and Breiger (1976), and Burt (1976, 1977) for partitioning actors in a network into nonoverlapping structurally equivalent sets. Blockmodeling algorithms such as CONCOR proceed by correlating the columns of a binary choice matrix so that individuals with similar patterns of ties with others come to be defined as structurally equivalent. The practice of stacking choice matrices for different kinds of ties so as to obtain a partitioning based on multiple networks is also characteristic of this strategy.